Genomotyping of Coxiella burnetii using microarrays reveals a conserved genomotype for hard tick isolates. - Quentin Leroy (Public Library of Science (PLoS), 2011)
C. burnetii is a Gram-negative intracellular Y-proteobacteria that causes the zoonotic disease Q fever. Q fever can manifest as an acute or chronic illness. Different typing methods have been previously developed to classify C. burnetii isolates to explore its pathogenicity. Here, we report a comprehensive genomotyping method based on the presence or absence of genes using microarrays. The genomotyping method was then tested in 52 isolates obtained from different geographic areas, different hosts and patients with different clinical manifestations. The analysis revealed the presence of 10 genomotypes organized into 3 groups, with a topology congruent with that obtained through multi-spacer typing. We also found that only 4 genomotypes were specifically associated with acute Q fever, whereas all of the genomotypes could be associated to chronic human infection. Serendipitously, the genomotyping results revealed that all hard tick isolates, including the Nine Mile strain, belong to the same genomotype.